Treatment of Hyperammonemia by Transplanting a Symbiotic Pair of Intestinal Microbes - Liu, Jing; Zhai, Chongkai; Rho, Jung-Rae; Lee, Sangbum; Heo, Ho Jin; Kim, Sangwoo; Kim, Hyeon Jin; Hong, Seong-Tshool (Frontiers in Cellular and Infection Microbiology, 2022)
Hyperammonemia is a deleterious and inevitable consequence of liver failure. However, no adequate therapeutic agent is available for hyperammonemia. Although recent studies showed that the pharmabiotic approach could be a therapeutic option for hyperammonemia, its development is clogged with poor identification of etiological microbes and low transplantation efficiency of candidate microbes. In this study, we developed a pharmabiotic treatment for hyperammonemia that employs a symbiotic pair of intestinal microbes that are both able to remove ammonia from the surrounding environment. By a radioactive tracing experiment in mice, we elucidated how the removal of ammonia by probiotics in the intestinal lumen leads to lower blood ammonia levels. After determination of the therapeutic mechanism, ammonia-removing probiotic strains were identified by high-throughput screening of gut microbes. The symbiotic partners of ammonia-removing probiotic strains were identified by screening intestinal microbes of a human gut, and the pairs were administrated to hyperammonemic mice to evaluate therapeutic efficacy. Blood ammonia was in a chemical equilibrium relationship with intestinal ammonia. Lactobacillus reuteri JBD400 removed intestinal ammonia to shift the chemical equilibrium to lower the blood ammonia level. L. reuteri JBD400 was successfully transplanted with a symbiotic partner, Streptococcus rubneri JBD420, improving transplantation efficiency 2.3×103 times more compared to the sole transplantation while lowering blood ammonia levels significantly. This work provides new pharmabiotics for the treatment of hyperammonemia as well as explains its therapeutic mechanism. Also, this approach provides a concept of symbiotic pairs approach in the emerging field of pharmabiotics.